Identification of Physics Concepts in Reog Ponorogo’s Dhadak Merak Dance as A Source of Learning Physics: An Analytical Study - Nur Iva Wulansari; Setyo Admoko (Universitas Lambung Mangkurat, 2021)
Indonesia is famous for its diverse cultures, and unwittingly from each culture has a different appeal. In the culture itself, there is a science that is not widely known by people, besides local wisdom from several regions can be used as a source of learning science. So far, science learning, especially in physics, still refers only to a handbook of teachers and students, where it contains science products in the form of facts, concepts, principles, theories, and laws and their application in the context of daily life. However, many books often contain contexts of daily life related to western culture that is not well recognized by Indonesian children, especially those in certain areas who still rely on nature as a learning media. Based on these problems, the aim to observe the application of physics in Indonesia's national culture. The researcher intended to identify the concept of equilibrium and moments force in the technique of the Dhadak Merak dance movement in Reog Ponorogo. This type of research is an analytical study by using documentation studies and the research target is Dhadak Merak Dance. Data collected by the observation method and analysis method using literature study and training video. According to the results of the research, physics concept studies were obtained, especially in equilibrium materials and moments force in the Dhadak Merak Dance, and learning with an ethnoscience approach has the potential for innovation learning to be applied in physics learning because it can train students science literacy and train students to think creatively.